2013
DOI: 10.4187/respcare.02812
|View full text |Cite
|
Sign up to set email alerts
|

The Science Guiding Selection of an Aerosol Delivery Device

Abstract: Aerosol therapy continues to be considered as one of the cornerstones of the profession of respiratory care, even after 60 years. Aerosol therapy serves as a critical intervention for both exacerbations and chronic maintenance for a variety of respiratory care conditions. Aerosol therapy uniquely blends both the art and science of medicine together to produce the practical and necessary clinical outcomes for patients with respiratory diseases. This review was presented as part of the New Horizons Symposium on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 40 publications
0
8
0
2
Order By: Relevance
“…25 Other factors that may influence the choice of an aerosol delivery device include the availability of the drug and device, personal preferences, convenience, the ability to use the device, the ability and necessity to regularly clean and replace SVNs, the cost to the patient, and the availability of competent caregivers. [26][27][28] A market survey conducted in 2008 indicated that almost half of patients with COPD had nebulizers and more than two thirds of such patients used nebulizers on a regular basis. 23 Thus, based on the prevalence of the disease, 29 millions of patients with COPD in the United States use nebulizers on a regular basis at home.…”
Section: Discussionmentioning
confidence: 99%
“…25 Other factors that may influence the choice of an aerosol delivery device include the availability of the drug and device, personal preferences, convenience, the ability to use the device, the ability and necessity to regularly clean and replace SVNs, the cost to the patient, and the availability of competent caregivers. [26][27][28] A market survey conducted in 2008 indicated that almost half of patients with COPD had nebulizers and more than two thirds of such patients used nebulizers on a regular basis. 23 Thus, based on the prevalence of the disease, 29 millions of patients with COPD in the United States use nebulizers on a regular basis at home.…”
Section: Discussionmentioning
confidence: 99%
“…An aerosol strategy, aerosol device, and delivery interface should be chosen based on: (1) availability of high-quality evidence obtained from human, animal, or bench studies; (2) device/interface efficiency; (3) ability of the patient to tolerate and coordinate respiratory effort with drug delivery; (4) patient preference; (5) cost of drug delivery; (6) whether the drug is approved to be used with a certain device or not; and (7) whether the device can be used safely with the form of respiratory support that the patient is receiving. 17,18 …”
Section: Clinical Considerations and Age-appropriate Administration Pmentioning
confidence: 99%
“…The vast majority of nebulizers used in adults are also used in children. Optimal particle size for most inhaled medications to achieve deposition in the periphery of the lung is 1-5 m. 18 Thus, an aerosol device should be chosen based on whether it can provide particles within this range. Aerosol devices that produce highly variable drug delivery or particles of Ͼ 5 m should be avoided because they may be more likely to deposit in children's upper airways, resulting in systemic absorption and potentially greater adverse effects (tachycardia).…”
Section: Aerosol Device Selectionmentioning
confidence: 99%
“…(17) Devices commonly used to treat URTIs generate droplets between 50 and 100 lm. These relatively large droplets remain in the upper respiratory tract and do not reach the lungs, and thus exerting their activity only where it is required, with marginal lung inhalation.…”
Section: Problems With the Use Of Aerosolized Antibioticsmentioning
confidence: 99%